Clinical utilisation of the Infant Monitor of vocal Production (IMP) for early identification of communication impairment in young infants at-risk of cerebral palsy: a prospective cohort study. (17th February 2022) - Ward, R; Hennessey, N; Barty, E; Elliott, C; Valentine, J; Cantle Moore, R
ABSTRACT: Aim: To report prospective longitudinal data of early vocaliszations of infants identified "at-risk" of cerebral palsy (CP) for early identification of communication impairment. Method: This case-control longitudinal prospective cohort study reports on the assessment of 36 infants, 18 identified as at-risk of CP at the time of enrolment and 18 typically developing (TD) children, at three time points: 6 months, 9 months and 12 months of age, Data were obtained through criterion and norm referenced assessments of vocaliszation behaviors. Results: Early vocal behaviors of infants identified as at-risk of CP did not differ from their age matched peers at 6 months of age, however, significant group differences emerged at 9 and 12 months when pre-canonical and canonical babble typically emerge. Generalized linear mixed models analysis showed that the rate of development of early language ability and more complex speech-related vocal behaviors was slower for infants at risk of CP when compared to TD infants, with over 75% of infants with CP showing below normal vocal production and impaired language by 12 months of age. Interpretation: Our data suggest characteristics of infant vocalizations associated with pre-canonical and canonical babbling provide a strong evidence base for predicting communication outcomes in infants at risk of CP.